Pengaruh Komunikasi Interpersonal Orang Tua-Anak Terhadap Agresi Siswa Kepada Guru - Issom, Fitri Lestari; Damayanti, Febi (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2020)
This research was conducted to find out the influence of parent-children interpersonal communication on student aggression to the teacher. This research used quantitative research method and the data are processed by using the regression analysis method. The population of this research are adolescent who studied in junior high school, senior high school, and vocational high school. The sample of this research are 360 students from junior high school, senior high school, and vocational high school in Central Jakarta. The instrument of this research is “The Aggression Questionnaire” which has been modified to devoted measuring student aggression to the teacher. Then, using the interpersonal communication scale to measure parent-children interpersonal communication. The result of this research shows that there are 4.4% of negative influence of interpersonal communication on students aggression to the teacher. It means that the more parent-children interpersonal communication happens, the more student aggression to the teacher decreases, and vice versa.